광각형광안저혈관조영술을 통한 베체트 포도막염 환자에서의 아달리무맙 치료효과 평가분석 - 이재협; 유형곤 (검안 및 콘택트렌즈 학회지, 21(3), 2022)
목적: 베체트 포도막염 환자에서 아달리무맙 치료를 시행한 후 광각형광안저혈관조영술을 통해 치료효과를 분석해보고자 한다. 대상과 방법: 베체트병으로 진단받고, 조절되지 않는 포도막염으로 아달리무맙 치료를 시작하여 30주 이상 경과 관찰하였던 17명의환자의 32안에 대해 후향적 의무기록 분석을 시행하였다. 광각형광안저혈관조영술을 통해 시신경유두 형광누출, 망막정맥 형광누출, 모세혈관 형광누출 등으로 나누어 포도막염의 상태를 평가하고, 혈관누출을 중심부와 주변부로 나누어 아달리무맙 치료 시작 이후30주까지의 치료 반응을 평가하였다. 결과: 아달리무맙 치료 시행 후 환자들의 최대교정시력과 초광각형광안저혈관조영술 점수는 6주, 14주, 30주 모두에서 유의한 감소를보였다. 형광누출의 경우 아달리무맙 치료 시작 전과 비교하여 치료 시작 후 30주째 망막정맥과 모세혈관의 형광누출은 현저히 줄었으나(p=0.032, p=0.004), 시신경유두 과형광은 상대적으로 지속되었다(p=0.083). 각 경과 관찰 시기마다 중심부 망막혈관 형광누출의 유의한 감소가 있었으나, 주변부 망막혈관 형광누출의 경우 0-6주, 6-14주, 14-30주 기간 동안 유의한 변화는 없었다. 결론: 베체트 환자의 포도막염 치료효과에 대한 평가 방법으로 광각형광안저혈관조영술을 이용할 수 있다. 망막혈관의 형광누출을파악하는 것이 중요하며 그 위치에 따라 누출 양상의 차이가 있다. Purpose: To investigate the role of ultra-widefield fluorescein angiography (UWFA) for monitoring the therapeutic response to adalimumab in patients with Behcet’s uveitis. Methods: Patients with Behcet’s uveitis treated with adalimumab for ≥ 30 weeks were included. The best-corrected visual acuity (BCVA), grading of anterior chamber cell, grading of vitreous haze, and UWFA findings were assessed at baseline, and at 6, 14, and 30 weeks from the start of adalimumab treatment. Results: A total of 32 eyes of 17 patients were included. There were significant decreases in BCVA and UWFA scores at 6, 14, and 30 weeks after adalimumab administration. UWFA scores for vascular and capillary leakage were decreased at 30 weeks (p = 0.032, p = 0.004), while the UWFA scores for disc hyperfluorescence persisted (p = 0.083). Although vascular and capillary leakage at the posterior pole was significantly decreased at 6, 14, and 30 weeks, there was no significant change of the score for peripheral vascular and capillary leakage from baseline to 6 weeks, from 6 to 14 weeks, and from 14 to 30 weeks. Conclusions: UWFA can be used to evaluate the treatment response of adalimumab in Behcet’s uveitis. The vascular leakage pattern varies depending on the location of retinal vessels. KCI Citation Count: 0